Sindicalismo revolucionario y primer gobierno de Yrigoyen Nuevas aproximaciones e hipótesis interpretativas - Koppmann, Walter; Belkin, Alejandro (Ariadna Ediciones, 2022)
With a marked revolutionary and workerist phraseology with libertarian overtones, the first revolutionary unionists in Argentina came from within the Socialist Party led by Juan B. Justo, within which they had challenged their growing electoral and parliamentary orientation, under the influence of the new ideas that they were beginning to gain ground in the French and Italian labor movement. At the beginning of the 20th century, intense social struggles in Argentina catalyzed this process of political differentiation, in the context of the first general strikes and direct confrontations with the state and the ruling class. During the following years, revolutionary syndicalism unfolded as a dynamic and ductile current within a recently formed, heterogeneous and highly ethnically fragmented labor movement. The book that we present here continues and advances on the investigations carried out in the last period, providing a set of original works that examine little-reported aspects of the Creole revolutionary syndicalist current during the period prior to the first government of Hipólito Yrigoyen (1916-1922), the mandate itself and the subsequent moment, already under the presidency of Marcelo T. de Alvear (1922-1928). Starting from a careful study of primary sources, the chapters investigate aspects such as: the syndicalist political formation prior to 1916; militancy and organization in the wood industry; the activation of revolutionary unionism among rural workers; the link between trade unionism and the world of women's work; the positions and struggles within the current around the state project of legal status for unions.